2005
DOI: 10.1002/mrc.1627
|View full text |Cite
|
Sign up to set email alerts
|

HPLC–NMR of fatty alcohol ethoxylates

Abstract: The application of HPLC-NMR for the analysis of a mixture of fatty alcohol ethoxylates (FAEs) is described. The use of the new generation, cryogenically cooled probes is investigated in respect of the sensitivity advantage that they provide. The FAE mixture is separated using liquid chromatography at the critical point of adsorption. The ability of the method to differentiate between the different end groups and the degree of polymerization of the mixture constituents is investigated. Both on-flow and stop-flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
1
22
1
Order By: Relevance
“…5. Peak assignment has already been confirmed by previous LC‐NMR experiments 24. The order of elution confirms a retention mechanism based on hydrophobic interactions.…”
Section: Resultssupporting
confidence: 75%
“…5. Peak assignment has already been confirmed by previous LC‐NMR experiments 24. The order of elution confirms a retention mechanism based on hydrophobic interactions.…”
Section: Resultssupporting
confidence: 75%
“…Further studies on coupled HPLC-NMR have shown the power of liquid adsorption chromatography (LAC) for the analysis of polymers regarding the chemical composition [8][9][10][11][12][13]. It was shown that polyethylene oxides can be analysed with regard to functionality type distribution by identifying the different end groups [8].…”
Section: Introductionmentioning
confidence: 98%
“…It was shown that polyethylene oxides can be analysed with regard to functionality type distribution by identifying the different end groups [8]. In particular, liquid chromatography at the critical point of adsorption coupled to NMR allows the full assignment of the chemical structure and the degree of polymerisation of all oligomer species [10,11]. The critical point of adsorption was also used for the analysis of tacticity of poly(ethyl methacrylate)s by HPLC-NMR [12].…”
Section: Introductionmentioning
confidence: 99%
“…Krämer et al reported about SEC-NMR for the chemical composition analysis of poly(styrene-cobutyl acrylate) copolymers [152]. Further studies on coupled HPLC-NMR have shown the power of liquid adsorption chromatography (LAC) for the analysis of polymers regarding the chemical composition [153][154][155][156][157][158]. It was shown that polyethylene oxides can be analyzed with regard to functionality type distribution by identifying the different endgroups [153].…”
Section: Coupling With 1 H-nmrmentioning
confidence: 99%
“…It was shown that polyethylene oxides can be analyzed with regard to functionality type distribution by identifying the different endgroups [153]. It has been shown that LCCC coupled to NMR allows for the full assignment of the chemical structure and the degree of polymerization of all 220 7 Hyphenation of Polymer Chromatography with Information-Rich Detectors oligomer species in complex mixtures [155,156]. sufficiently high flow rate, moderate sample concentration, and on-flow detection.…”
Section: Coupling With 1 H-nmrmentioning
confidence: 99%